STUDENT'S INTENTION TOWARDS SUSTAINABLE AND RESPONSIBLE CLOTHING CONSUMPTION - Aisyah Dewi Muthi'ah (Journal of Industrial Engineering Management, 2021)
The textile industry is contributing a lot to the climate change since human consumptions on textile is very high. This articles aims to measure the influence of student’s sustainability knowledge and demographic profiles to their intention on buying sustainability product. Students from the same faculty completed an online survey with a total of 315 valid response that assesed the purchasing level, reasons, priorities, as well as some sustainable behaviour that the respondent might have. An ordinal regression used with employing the SPSS 16 software and p=0.05. Results suggest that the most significant factors affecting the students purchasing intention on sustainable products was whether their consider sustainable material as priority when purchasing textile products or not.